Efektivitas Mentimeter sebagai Media Pembelajaran Interaktif di Kelas X IBB 1 SMAN 1 Kintamani - Ni Nengah Mirayani; I Nyoman Yasa; I Nyoman Sudiana (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This study aims to (1) describe the implementation of the use of Mentimeter as an interactive learning medium in negotiating text material in class X IBB 1 SMAN 1 Kintamani, (2) describe the effectiveness of using Mentimeter as an interactive learning medium in negotiating text material in class X IBB 1 SMAN 1 Kintamani negotiating text material in class X IBB 1 SMAN 1 Kintamani, (3) describing the factors that inhibit and support Mentimeter as an interactive learning medium in negotiating text material in class X IBB 1 SMAN 1 Kintamani. The data was collected using the methods of observation, interviews, and documentation, and analyzed using descriptive-qualitative methods. The subjects of this study were students and teachers of class X IBB 1 SMAN 1 Kintamani, while the object of this study was the effectiveness of the Mentimeter as an interactive learning medium for negotiating text material in class X IBB 1 SMAN 1 Kintamani. The results showed that (1), Mentimeter has been used optimally and received a positive response from students (2), Mentimeter proved to be effective with an average value of 80.00 and (3) there are several obstacles and supporters of the use of Mentimeter. Based on the conclusions, suggestions submitted to other researchers are expected to conduct similar research but with different concepts so that more theories are found.